Air Pollution Tolerance Index of Some Tree Species of Pashupati and Budhanilkantha Area, Kathmandu - Ter, Sabita; Chettri, Mukesh K.; Shakya, Kumudini (Amrit Research Journal, 2020)
The present study aims to assess the air pollution tolerant trees from the roadside of Pashupati area of Kathmandu exposed to vehicular air pollution. This area with heavy traffic density was considered as the polluted site and Budhanilkantha, lying at the outskirt of Kathmandu with very less traffic density was considered as the less-polluted site and was selected as the control site of the study. Commonly available 21 roadside same tree species from both polluted and control sites were chosen. Air pollution tolerance index (APTI) values of the trees were calculated considering the biochemical parameters - relative water content, total leaf chlorophyll, ascorbic acid and leaf extract pH by using standard method. Significantly higher APTI values (P ≤ 0.05) were obtained in Cinnamomum camphora, Ficus elastica, F. religiosa, F. benghalensis and Grevillea robusta indicating that they are tolerant tree species. Phyllanthus emblica and Schima wallichii were found to be sensitive tree species.